Comprehensive Transcriptome Analyses Reveal Differential Gene Expression Profiles of Camellia sinensis Axillary Buds at Para-, Endo-, Ecodormancy, and Bud Flush Stages - Hao, Xinyuan; Yang, Yajun; Yue, Chuan; Wang, Lu; Horvath, David P.; Wang, Xinchao (Frontiers in Plant Science, 2017)
Winter dormancy is an important biological feature for tea plant to survive cold winters, and it also affects the economic output of tea plant, one of the few woody plants in the world whose leaves are harvested and one of the few non-conifer evergreen species with characterized dormancies. To discover the bud dormancy regulation mechanism of tea plant in winter, we analyzed the global gene expression profiles of axillary buds at the paradormancy, endodormancy, ecodormancy and bud flush stages by RNA-Seq analysis. In total, 16,125 differentially expressed genes (DEGs) were identified among the different measured conditions. Gene set enrichment analysis was performed on the DEGs identified from each dormancy transition. Enriched gene ontology (GO) terms, gene sets and transcription factors were mainly associated with epigenetic mechanisms, phytohormone signaling pathways, and callose-related cellular communication regulation. Furthermore, differentially expressed transcription factors as well as chromatin- and phytohormone-associated genes were identified. GI-, CAL-, SVP-, PHYB-, SFR6-, LHY-, ZTL-, PIF4/6-, ABI4-, EIN3-, ETR1-, CCA1-, PIN3-, CDK- and CO-related gene sets were enriched. Based on sequence homology analysis, we summarized the key genes with significant expression differences in poplar and tea plant. The major molecular pathways involved in tea plant dormancy regulation are consistent with those of poplar to a certain extent; however, the gene expression patterns varied. This study provides the global transcriptome profiles of overwintering buds at different dormancy stages and is meaningful for improving the understanding of bud dormancy in tea plant.